Analyzing the intervening sequences of pluripotency associated genes to identify conserved Sequence patterns in human using Integrative bioinformatics - PRIYANKA NARAD; GULSHAN WADHWA; KAILASH C UPADHYAYA (International Journal of Pharma and Bio Sciences, 2017)
The identification of conserved regions in the set of genes responsible for maintenance of pluripotency in human is essential for identifying their mode of action. To understand the mechanism of transcriptional regulation in a complicated phenomenon like pluripotency, it is indispensable to identify and characterize the intervening region of the major genes responsible for maintenance of pluripotency. We identified 56 genes responsible for pluripotency using the available literature and searching databases. The region corresponding to 1000bp from the start site of the gene was retrieved for motif analysis. These set of sequences were submitted to the MEME suite for comprehensive analysis. We identified 5 conserved motifs which had occurrence in the intervening region of all the 56 sequences. This indicated that these motifs served an important role for all of these 56 genes. These motifs were compared to known transcription factor database such as HOCOMOCO, which gave us matches with TFs which have not been reported previously to be reported in early developmental stages in human. Expression analysis of these motifs across the developmental timeline indicate that they have a role in the early stage of development from the oocyte to the 6 celled stages and were down-regulated as soon as the cell enters the pluripotent state. As an inference, we propose that these TFs potentiate the genes responsible for pluripotency by maintaining their cell cycle and growth stages. Any malfunction in the expression profile of these TFs would probably block the genes to enter the pluripotent state.